Data Driven Business Transformation - Jackson, Peter; Carruthers, Caroline (Ascent Audio, 2019)
The organizations that harness the power of data to transform their businesses will be the market leaders. You can be sure that your competitors will be looking for insights in their data to drive them ahead and that the disruptors in your sector will be data driven. Data, if used correctly, has the power to transform your business and make you the market leader. Data Driven Business Transformation is the practical guide to harnessing your data to compete and thrive in today's dynamic marketplace. This essential resource provides the insight, knowledge and focus you require to transform your business-unlocking the power of data and revealing its hidden value. Delivering step-by-step instructions to every stage of data transformation, this book enables you to strengthen your data literacy and make effective data-driven decisions. The digital revolution has proven challenging for many businesses. Once viewed as the solution, technology is oftentimes the problem-driving business online but failing to exploit the data to drive operations and value. Authors Peter Jackson and Caroline Carruthers draw from their practical experience as Chief Data Officers to present strategies and methods to unleash the transformational power of data.
Online resource; Title from title page (viewed May 21, 2019)
Keywords: Business; Affaires; businesses (business enterprises); Audiobooks